ABO-blood groups and outcomes after abdominal aortic aneurysm repair - Teresa Manuel Santos Cruz Machado (2022)
Purpose: To analyze the association between the blood groups and long-term outcomes after abdominal aortic aneurysm (AAA) repair. Methods: Retrospective cohort study that included consecutive patients submitted to elective AAA surgery (2009-2019). Outcomes were patient survival, and freedom from major adverse cardiac events (MACE). Results: From a total of 333 patients, 49.5% were blood type A, followed by 39.3% O, 8.1% B and 3.1% AB, while 82.4% were Rh+ and 17.6% Rh-. The distribution of the blood phenotypes was similar between AAA patients and the Portuguese population. The median follow-up time was 75.4 months (interquartile range 65.8-81.6). Patient survival at 1 and 5 years was 89.3% (95%Confidence Interval 86.0-92.7%) and 61.9% (56.2-68.2%), respectively. MACE-free survival at 1 and 5 years was 85.7% (81.9-89.5%) and 57.6% (51.9-64%), respectively. Survival and MACE-free survival was similar between blood group types. Age, maximum aortic diameter, peripheral arterial disease and chronic obstructive pulmonary were independent positive predictors of all-cause mortality. Maximum aortic diameter, estimated glomerular filtration rate, cerebrovascular disease and type of surgery were independent predictors of MACE-free survival. Conclusion: We did not find any association between the blood types and the presence of AAA nor with the main outcomes after AAA repair.